Kohesi Kepemimpinan Gideon dan Sisi Negatif Kekuasaanya Berdasarkan Hakim-Hakim 8:22-35 - Pattinaja, Aska Aprilano; Lesnussa, Johny (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
This study is the antithesis of many studies on Gideon that praise and position him as a great leader. It is ironic that Gideon turned out to have a bad legacy to Israel as a result of the cohesion between leadership and the negative side of power and this is rarely exposed by researchers. The purpose of this study is to examine the factors of Gideon's failure and make it an important lesson for leaders to have the right character so that they can reach the end of good leadership (finishing well). Based on the hermeneutic method with a literature study approach, this article finds several negative factors of Gideon, namely: first, unstable emotions triggered controversial decisions as a slaughterer; second, leaving a legacy that led the Israelites to fall into the worship of ephods as idols; and third, having a high lust for power so that he named his son Abimelech, who later became king through intrigue and murder. The results of this study are very useful as an important lesson to every believer, that even though leaders are chosen by God, but as humans they still have weaknesses, so they should not be worshiped excessively.